2009
DOI: 10.1080/10826070903091654
|View full text |Cite
|
Sign up to set email alerts
|

Enantioanalysis of Tertatolol in Plasma and Pharmaceutical Formulations with Immobilized Polysaccharide-Derived HPLC Chiral Column at Nano-detection Level

Abstract: A sensitive and selective high performance liquid chromatography (HPLC) method has been developed for the simultaneous determination of tertatolol enantiomers in plasma and pharmaceutical formulations. Enantiomeric resolution was achieved on cellulose tris(3,5-dichlorophenylcarbamate) immobilized onto 5 mm, spherical porous silica chiral stationary phase (CSP) known as Chiralpak IC with UV detection set at 254 nm. The mobile phase which consisted of n-hexane-ethanol-triethylamine (60:40:0.1%, v=v=v) was used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…The polar ionic mode (PIM) has been described as a novel mobile phase to obtain difficult enantioselective separation with macrocyclic antibiotic-based chiral stationary phases. 30 This approach uses a non-aqueous polar component (methanol) with glacial acetic acid or trifluoroacetic acid and an amine such as triethylamine which are necessary to achieve enantioseparation. In this study, baseline separation of the tertatolol enantiomers was achieved on the vancomycin CSP with a polar ionic mobile phase consisted of methanol-glacial acetic acid-triethylamine (100:0.01:0.015, v/ v/v) ( Table 1).…”
Section: Results and Discussion Optimization Of The Chromatographic Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The polar ionic mode (PIM) has been described as a novel mobile phase to obtain difficult enantioselective separation with macrocyclic antibiotic-based chiral stationary phases. 30 This approach uses a non-aqueous polar component (methanol) with glacial acetic acid or trifluoroacetic acid and an amine such as triethylamine which are necessary to achieve enantioseparation. In this study, baseline separation of the tertatolol enantiomers was achieved on the vancomycin CSP with a polar ionic mobile phase consisted of methanol-glacial acetic acid-triethylamine (100:0.01:0.015, v/ v/v) ( Table 1).…”
Section: Results and Discussion Optimization Of The Chromatographic Cmentioning
confidence: 99%
“…Recently, Hefnawy et al reported enantioanalysis of tertatolol in human plasma and pharmaceutical formulations using immobilized polysaccharide-derived HPLC chiral stationary phase known as Chiralpak IC column. 30 Reviewing the literature revealed that up to present time, no study has yet published concerning analysis of tertatolol enantiomers utilizing macrocyclic antibiotic CSPs.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of pindolol enantiomers in plasma and pharmaceutical products by HPLC with fluorescence detection was accomplished using a Chiralpak IB column . The Chiralpak IC CSP was used in the HPLC enantioanalysis of tertalolol enantiomers and also in the direct HPLC enantioseparation of terazosin .…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…Essas fases estacionárias apresentam excelente habilidade de reconhecimento quiral para uma série de compostos com diferentes propriedades físico-químicas. [78][79][80] Devido ao alto poder de enantiorresolução e grande estabilidade, as CSPs baseadas em derivados de polissacarídeos, adsorvidos ou quimicamente ligados ao suporte, têm sido utilizadas na quantificação de enantiômeros em matrizes biológicas [81][82][83][84] e para separações em escala semi-preparativa e preparativa.…”
Section: Figura 3 Seletor Quiral Naftiletilcarbamato De B-ciclodextrunclassified